imported>Paul Wormer |
imported>Paul Wormer |
Line 107: |
Line 107: |
| The quantum mechanical virial theorem follows | | The quantum mechanical virial theorem follows |
| :<math> | | :<math> |
| 2\langle T\rangle = -\sum_{j=1}^n \langle \mathbf{r}_j \cdot\mathbf{F}_j \rangle
| | \langle T\rangle = -\tfrac{1}{2} \sum_{j=1}^n \langle \mathbf{r}_j \cdot\mathbf{F}_j \rangle |
| </math> | | </math> |
| where ⟨ … ⟩ stands for an expectation value with respect to the exact eigenfunction Ψ of ''H''. | | where ⟨ … ⟩ stands for an expectation value with respect to the exact eigenfunction Ψ of ''H''. |
Line 125: |
Line 125: |
|
| |
|
| For instance, for a stable atom (consisting of charged particles with Coulomb interaction): ''k'' = −1, and hence 2⟨''T'' ⟩ = −⟨''V'' ⟩. | | For instance, for a stable atom (consisting of charged particles with Coulomb interaction): ''k'' = −1, and hence 2⟨''T'' ⟩ = −⟨''V'' ⟩. |
| | |
| ==Reference== | | ==Reference== |
| <references /> | | <references /> |
Revision as of 16:22, 15 February 2010
In mechanics, a virial of a stable system of n particles is a quantity proposed by Rudolf Clausius in 1870.[1]
The virial (from the Latin vis, force) is defined by
![{\displaystyle -{\tfrac {1}{2}}\sum _{i=1}^{n}\mathbf {r} _{i}\cdot \mathbf {F} _{i},}](https://wikimedia.org/api/rest_v1/media/math/render/svg/79aab49651d9091cb183bb4060aa3e5a06bd1ba5)
where Fi is the total force acting on the i th particle and ri is the position of the i th particle; the dot stands for an inner product between the two 3-vectors. Indicate long-time averages by angular brackets. The importance of the virial arises from the virial theorem, which connects the long-time average of the virial to the long-time average ⟨ T ⟩ of the total kinetic energy T of the n-particle system,[2]
![{\displaystyle \langle T\rangle =-{\tfrac {1}{2}}\sum _{i=1}^{n}\langle \mathbf {r} _{i}\cdot \mathbf {F} _{i}\rangle .}](https://wikimedia.org/api/rest_v1/media/math/render/svg/9d9a3bc36ecf6b579313879227870d423aa8df5f)
Proof of the virial theorem
Consider the quantity G defined by
![{\displaystyle G\equiv \sum _{i=1}^{n}\mathbf {r} _{i}\cdot \mathbf {p} _{i}\quad {\hbox{with}}\quad \mathbf {p} _{i}=m_{i}{\frac {d\mathbf {r} _{i}}{dt}}.}](https://wikimedia.org/api/rest_v1/media/math/render/svg/a626e0792191b704c0f3bf8d645f6c83d93243d5)
The vector pi is the momentum of particle i. Differentiate G with respect to time:
![{\displaystyle {\frac {dG}{dt}}=\sum _{i=1}^{n}\left[{\frac {d\mathbf {r} _{i}}{dt}}\cdot \mathbf {p} _{i}+\mathbf {r} _{i}\cdot {\frac {d\mathbf {p} _{i}}{dt}}\right]}](https://wikimedia.org/api/rest_v1/media/math/render/svg/0507e3de450ad74d28e52655ef118e8036ae0c28)
Use Newtons's second law and the definition of kinetic energy:
![{\displaystyle \mathbf {F} _{i}={\frac {d\mathbf {p} _{i}}{dt}}\quad {\hbox{and}}\quad 2T_{i}={\frac {d\mathbf {r} _{i}}{dt}}\cdot \mathbf {p} _{i}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/2d2f5293c81c6de59d4a8fb0f00914f4ce503b17)
and it follows that
![{\displaystyle {\frac {dG}{dt}}=2T+\sum _{i=1}^{n}\mathbf {r} _{i}\cdot \mathbf {F} _{i}\quad {\hbox{with}}\quad T\equiv \sum _{i=1}^{n}T_{i}.}](https://wikimedia.org/api/rest_v1/media/math/render/svg/e352ec5868d4ac2e744ff7ed038b198f15d97fba)
Averaging over time gives:
![{\displaystyle \left\langle {\frac {dG}{dt}}\right\rangle \equiv {\frac {1}{T}}\int _{0}^{T}{\frac {dG}{dt}}dt={\frac {1}{T}}\left[G(T)-G(0)\right].}](https://wikimedia.org/api/rest_v1/media/math/render/svg/1b1557f88d7e99f2ff2e4e8d38f5dfa015b34a9c)
If the system is stable, G(t) at time t = 0 and at time t = T is finite. Hence, if T goes to infinity, the quantity on the right hand side goes to zero. Alternatively, if the system is periodic with period T, G(T) = G(0) and the right hand side will also vanish. Whatever the cause, we assume that the time average of the time derivative of G is zero, and hence
![{\displaystyle 2\langle T\rangle +\sum _{i=1}^{n}\langle \mathbf {r} _{i}\cdot \mathbf {F} _{i}\rangle =0,}](https://wikimedia.org/api/rest_v1/media/math/render/svg/7269d0ff8c8ca72a27d482770652f6936faa4acb)
which proves the virial theorem.
Application
An interesting application arises when the potential V is of the form
![{\displaystyle V=\sum _{i=1}^{n}V(\mathbf {r} _{i})\quad {\hbox{with}}\quad V(\mathbf {r} _{i})=a_{i}r_{i}^{k}\quad {\hbox{and}}\quad r_{i}=(x_{i}^{2}+y_{i}^{2}+z_{i}^{2})^{1/2},}](https://wikimedia.org/api/rest_v1/media/math/render/svg/5bf4ae450fe367e364766daf545d79c17b2cc176)
where ai is some constant (independent of space and time).
An example of such potential is given by Hooke's law with k = 2 and Coulomb's law with k = −1.
The force derived from a potential is
![{\displaystyle \mathbf {F} _{i}=-{\boldsymbol {\nabla }}_{i}V\equiv -\left({\frac {\partial V}{\partial x_{i}}},\;{\frac {\partial V}{\partial y_{i}}},\;{\frac {\partial V}{\partial z_{i}}}\right)}](https://wikimedia.org/api/rest_v1/media/math/render/svg/4250043e8ed7ee97c0efa75e401250da1675e423)
Consider
![{\displaystyle {\frac {\partial V}{\partial x_{i}}}=a_{i}{\frac {\partial (r_{i})^{k}}{\partial x_{i}}}=a_{i}k(r_{i})^{k-1}{\frac {\partial r_{i}}{\partial x_{i}}}=a_{i}k(r_{i})^{k-1}{\frac {x_{i}}{r_{i}}}=k{\frac {x_{i}}{r_{i}^{2}}}V(\mathbf {r} _{i}).}](https://wikimedia.org/api/rest_v1/media/math/render/svg/514c5200baf1f80993855290b77da5b2b06d57c3)
Hence
![{\displaystyle \mathbf {F} _{i}=-kV(\mathbf {r} _{i}){\frac {\mathbf {r} _{i}}{r_{i}^{2}}}.}](https://wikimedia.org/api/rest_v1/media/math/render/svg/f87bd0dd86c1be018683f04c589da5082a2de0af)
Then applying this for i = 1, … n,
![{\displaystyle 2\langle T\rangle =k\sum _{i=1}^{n}\left\langle V(\mathbf {r} _{i})\cdot {\frac {\mathbf {r} _{i}\cdot \mathbf {r} _{i}}{r_{i}^{2}}}\right\rangle =k\langle V\rangle \quad {\hbox{where}}\quad V=\sum _{i=1}^{n}V(\mathbf {r} _{i}).}](https://wikimedia.org/api/rest_v1/media/math/render/svg/0063d32cccc5136a012f0cf1f49c54bd1247129e)
For instance, for a system of charged particles interacting through a Coulomb interaction:
![{\displaystyle 2\langle T\rangle =-\langle V\rangle .}](https://wikimedia.org/api/rest_v1/media/math/render/svg/99afa1e7840395ff6ed23a76af4d767312691d6e)
Quantum mechanics
The virial theorem holds also in quantum mechanics. Quantum mechanically the angular brackets do not indicate a time-average, but an expectation value with respect to an exact stationary eigenstate of the Hamiltonian of the system. The theorem will be proved and applied to the special case of a potential that has a rk-like dependence. Everywhere Planck's constant ℏ is taken to be one.
Let us consider a n-particle Hamiltonian of the form
![{\displaystyle H=T+V(\mathbf {r} _{1},\mathbf {r} _{2},\ldots ,\mathbf {r} _{n})\quad {\hbox{with}}\quad T=\sum _{j=1}^{n}{\frac {\mathbf {p} _{j}\cdot \mathbf {p} _{j}}{2m_{j}}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/f0f1bf5521acf18ec2dbf8e407b0bfe941882b5e)
where mj is the mass of the j-th particle. The momentum operator is
![{\displaystyle \mathbf {p} _{j}=-i{\boldsymbol {\nabla }}_{j},\qquad (\hbar =1).}](https://wikimedia.org/api/rest_v1/media/math/render/svg/aededc72cd675388ee9ce7c64564f8695797519c)
Using the self-adjointness of H and the definition of a commutator one has for an arbitrary operator G,
![{\displaystyle 0=\langle \Psi |[G,H]|\Psi \rangle \quad {\hbox{with}}\quad H|\Psi \rangle =E|\Psi \rangle .}](https://wikimedia.org/api/rest_v1/media/math/render/svg/56f4b13d045b7ea141546ab1196c0b3d7a567ef1)
In order to obtain the virial theorem, we consider
![{\displaystyle G=\sum _{k=1}^{n}\mathbf {r} _{k}\cdot \mathbf {p} _{k}.}](https://wikimedia.org/api/rest_v1/media/math/render/svg/4328cc84f9ebb7fadabbb075787ba82af1af8707)
Use
![{\displaystyle [\mathbf {r} _{k}\cdot \mathbf {p} _{k},H]=[\mathbf {r} _{k},T]\cdot \mathbf {p} _{k}+\mathbf {r} _{k}\cdot [\mathbf {p} _{k},V]}](https://wikimedia.org/api/rest_v1/media/math/render/svg/91461abed3221bbe78fa28a3a87b4b62274ee85e)
Define
![{\displaystyle \mathbf {F} _{k}\equiv -i[\mathbf {p} _{k},V]=-[{\boldsymbol {\nabla }}_{k},V].}](https://wikimedia.org/api/rest_v1/media/math/render/svg/4e287a143cbf259ba321222f19da27ae8c06d4ec)
Use
![{\displaystyle [r_{k\alpha },p_{j\beta }^{2}]=\delta _{kj}\delta _{\alpha \beta }2ip_{k\alpha },\quad \alpha ,\beta =x,y,z;\quad k,j=1,,2,\ldots ,n,}](https://wikimedia.org/api/rest_v1/media/math/render/svg/1c16a3f3e08c1f719475c5f78a7fb0bb9010652a)
and we find
![{\displaystyle [G,H]=i{\big (}2T+\sum _{j=1}^{n}\mathbf {r} _{j}\cdot \mathbf {F} _{j}{\big )}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/c723376beae04e51e917dd2ccc2bc06db10d8346)
The quantum mechanical virial theorem follows
![{\displaystyle \langle T\rangle =-{\tfrac {1}{2}}\sum _{j=1}^{n}\langle \mathbf {r} _{j}\cdot \mathbf {F} _{j}\rangle }](https://wikimedia.org/api/rest_v1/media/math/render/svg/2e1bccf2b7b345e223fd7efa9ad81df145bb521a)
where ⟨ … ⟩ stands for an expectation value with respect to the exact eigenfunction Ψ of H.
If V is of the form
![{\displaystyle V=\sum _{j=1}^{n}a_{j}(r_{j})^{k},}](https://wikimedia.org/api/rest_v1/media/math/render/svg/1265195b9d8ecb15e68d00f0da2d36b299a699c6)
it follows that
![{\displaystyle \mathbf {F} _{j}=-[{\boldsymbol {\nabla }}_{j},V]=-a_{j}\,k\mathbf {r} _{j}\,(r_{j})^{k-2}.}](https://wikimedia.org/api/rest_v1/media/math/render/svg/f8eb3032df63034b1697afc8e1dea13b33d2ca24)
From this:
![{\displaystyle 2\langle T\rangle =k\sum _{j=1}^{n}a_{j}\langle (\mathbf {r} _{j}\cdot \mathbf {r} _{j})\,(r_{j})^{k-2}\rangle =k\langle V\rangle }](https://wikimedia.org/api/rest_v1/media/math/render/svg/2edd520d5c541713ca4ceb070bc30534acda7cff)
For instance, for a stable atom (consisting of charged particles with Coulomb interaction): k = −1, and hence 2⟨T ⟩ = −⟨V ⟩.
Reference
- ↑ R. Clausius, On a Mechanical Theorem applicable to Heat, The London, Edinburgh, and Dublin Philosophical Magazine and Journal of Science, vol. 40, 4th series, pp. 122 – 127 (1870). Google books. Note that Clausius still uses the term vis viva for kinetic energy, but does include the factor ½ in its definition, following Coriolis.
- ↑ Clausius states this result as: the mean vis viva of the system is equal to its virial.